Hubungan Lama Hemodialisa dengan Kepatuhan Diet Cairan pada Pasien Gagal Ginjal Kronis - Mimi Amaludin; Nurpratiwi Nurpratiwi; Defa Arisandi; Ali Akbar; Uti Rusdian Hidayat; Fauzan Alfikrie; Debby Hatmalyakin (Malahayati Nursing Journal, 2025)
ABSTRACT Chronic kidney disease (CKD) is an irreversible condition associated with increased morbidity and mortality rates, typically arising as a consequence of diabetes mellitus and hypertension. The height of management of chronic kidney disease (CKD) is hemodialysis therapy. Hemodialysis is provided to individuals with CKD necessitating long-term or permanent treatment. Patients with chronic kidney disease getting hemodialysis have to keep up with fluid management protocols. This study aims to ascertain the correlation between the duration of hemodialysis and adherence to fluid dietary restrictions in chronic kidney disease patients. The cross-sectional study design attempts to ascertain the correlation between the length of hemodialysis and adherence to a fluid diet in patients with chronic kidney disease (CKD). The study population includes cognitively intact CKD patients undergoing hemodialysis, with total sampling. The chi-square test was used for data analysis. The analysis, with a p-value of 0.000, indicates a correlation between the duration of hemodialysis and fluid diet adherence in chronic kidney disease patients receiving hemodialysis. Regular and continuous hemodialysis therapy affects patients' compliance with fluid dietary restrictions. Keywords: CKD, Compliance, Duration of Hemodialysis, Fluid Diet  ABSTRAK Penyakit GGK tidak dapat disembuhkan dan memiliki morbiditas serta mortalitas tinggi yang umumnya merupakan komplikasi dari penyakit diabetes melitus dan hipertensi. Penanganan akhir kondiri dari GGK adalah terapi hemodialisis. Hemodialisis dilakukan pada pasien GGK yang membutuhkan terapi jangka panjang atau terapi permanen. Pasien GGK yang menjalani hemodialisa diharuskan untuk patuh dalam melakukan manajemen cairan. Penelitian ini bertujuan untuk mengetahui hubungan lama hemodialisa dengan kepatuhan diet cairan pada pasien GGK. Desain penelitian cross sectional untuk mengetahui hubungan lama hemodialisa dengan kepatuhan diet cairan pada pasien GGK. Populasi penelitian ini adalah pasien GGK yang menjalani hemodialisa, kesadaran composmentis dengan pengambilan sampel menggunakan total sampling. Analisis data dilakukan menggunakan uji chi-square. Berdasarkan hasil analisis dengan nilai p-value 0,000 yang artinya terdapat hubungan lama hemodialisa terhadap kepatuhan diet cairan pada pasien GGK yang menjalani hemodialisa. Terapi hemodialisa yang dilakukan secara rutin dan terus menerus berdampak kepada kepatuhan pasien dalam melakukan diet cairan.   Kata Kunci: Diet Cairan, GGK, Kepatuhan, Lama Hemodialisa